Cross-cutting principles for planetary health education - Stone, Sara B.; Myers, Samuel S.; Golden, Christopher D.; Hunter, D. (Elsevier, 2018)
Since the 2015 launch of the Rockefeller Foundation Lancet Commission on planetary health,1 an enormous groundswell of interest in planetary health education has emerged across many disciplines, institutions, and geographical regions. Advancing these global efforts in planetary health education will equip the next generation of scholars to address crucial questions in this emerging field and support the development of a community of practice. To provide a foundation for the growing interest and efforts in this field, the Planetary Health Alliance has facilitated the first attempt to create a set of principles for planetary health education that intersect education at all levels, across all scales, and in all regions of the world—ie, a set of cross-cutting principles. These 12 cross-cutting principles (panel) are envisioned to be a set of core messages that every educator teaching planetary health at any level should strive to impart upon their students. These principles of planetary health education will act as overarching and wide ranging guiding themes for any educational setting, rather than as specific and measurable objectives that are audience dependent. These principles are intended to act as a base for curricular development and as a tool to guide education efforts in this emerging field; however, they should not be considered to be all-encompassing principles or equally important across all educational settings. Incorporating these principles into planetary health education efforts around the world should allow for a shared basis of understanding across disciplines, geographical regions, and cultures teaching planetary health. The cross-cutting principles were established through a series of five interactive sessions with the 137 members of the Planetary Health Education Brainstorm Group who are from all over the world and involved in education efforts at the intersection of health and environmental change (appendix).